Purification of recombinant peritrophic membrane proteins of the Old World Screwworm fly, Chrysomya bezziana - Roger Pearson; Sri Muharsini; Gene Wijffels; Tony Voucoloco (Indonesian Center for Animal Research and Development (ICARD), 2000)
To evaluate the feasibility of vaccinating sheep against the Old World Screwworm fly Chrysomya bezziana several recombinant peritrophin proteins were expressed in either a denatured form in Escherichia coli or a native-like form in Pichia pastoris cultures. Purification of the hexaHis tagged proteins was achieved by immobilized metal affinity chromatography. Proteins purified under reducing conditions were refolded using a glutathione shuffle procedure. Purification of a glutathione-Stransferase fusion protein was attempted using glutathione affinity chromatography in conjunction with anion exchange chromatography. The authenticity of the expressed proteins was verified by amino terminal amino acid sequencing. Carbohydrate analysis using biotinylated lectins revealed that Cb-peritrophin-48 expressed in Pichia pastoris was glycosylated with high mannose-type sugars. Four of the purified recombinant proteins were used to evaluate their protective immunogenicity in sheep against Chrysomya bezziana strike. Key words: Screwworm fly, Chrysomya bezziana, recombinant proteins, immobilized metal affinity chromatography